2014
DOI: 10.1088/1751-8113/48/2/025302
|View full text |Cite
|
Sign up to set email alerts
|

Generalized probabilistic theories and conic extensions of polytopes

Abstract: Generalized probabilistic theories (GPT) provide a general framework that includes classical and quantum theories. It is described by a cone C and its dual C * . We show that whether some one-way communication complexity problems can be solved within a GPT is equivalent to the recently introduced cone factorisation of the corresponding communication matrix M . We also prove an analogue of Holevo's theorem: when the cone C is contained in R n , the classical capacity of the channel realised by sending GPT state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…The upper bound of N 2 (the left-hand side of (27)) follows from the fact that the classical capacity of any GPT is bounded by the log 2 of the dimension of the state space [28], which in the case of entangled states for a pair of HST systems, as defined above, is N 2 .Thus, the gap we exhibit between single system classical capacity and two system classical capacity is close to optimal.…”
Section: Hyperdense Coding In Hstsmentioning
confidence: 79%
“…The upper bound of N 2 (the left-hand side of (27)) follows from the fact that the classical capacity of any GPT is bounded by the log 2 of the dimension of the state space [28], which in the case of entangled states for a pair of HST systems, as defined above, is N 2 .Thus, the gap we exhibit between single system classical capacity and two system classical capacity is close to optimal.…”
Section: Hyperdense Coding In Hstsmentioning
confidence: 79%
“…the collection of states, probabilities, and effects that are used. The argument is related to that used in [42] to show that extremal measurements have at most 3 effects. To prove it, first note that if ω(x) is not extremal, we can decompose it into extremal states ω(x) = i p i|x ω i .…”
Section: Proof Of Lemmamentioning
confidence: 90%
“…However in [42] it was shown that by refining a measurement, and decomposing a measurement into a convex combination of other measurements, one can restrict to measurements with at most 3 effects all proportional to the extremal effects.…”
Section: Polygon Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, cone programming is a natural tool to have handy when studying post-quantum theories. Although cone programming is a well-studied area of optimisation theory, it has only had a small number of applications in quantum theory [3,16,22,26,32] and in GPTs [2,14,19,21,31]. We hope this work will inspire future applications of cone programming in the study of GPTs and solidify it as an indispensable mathematical tool.…”
Section: Introductionmentioning
confidence: 90%